2019
DOI: 10.1007/s13187-019-01567-6
|View full text |Cite
|
Sign up to set email alerts
|

The Knowledge, Attitude, and Self-Reported Behaviors of Oncology Physicians Regarding Fertility Preservation in Adult Cancer Patients

Abstract: There is a growing concern about the fertility preservation for adult cancer patients of reproductive age. Very little literature exists about fertility preservation of cancer survivors in Chinese text. This study is first to describe the knowledge level, attitude, and practice behaviors among physicians concerning fertility preservation in adult cancer patients in China. A cross-sectional survey with 30-item was conducted to assess Chinese oncology physicians' knowledge, attitude, and behaviors regarding fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…Several relative factors were found to hinder the discussion of FP for clinicians such as lack of knowledge, cultural and religious limitations, feeling uncomfortable, and lack of communication skills [39][40][41]. However, although all programs in this review provided FP-related knowledge for healthcare providers, communication strategies and psychosocial support were only taught in two programs, and FP-related ethical and legal issues were only mentioned in one program.…”
Section: Discussionmentioning
confidence: 94%
“…Several relative factors were found to hinder the discussion of FP for clinicians such as lack of knowledge, cultural and religious limitations, feeling uncomfortable, and lack of communication skills [39][40][41]. However, although all programs in this review provided FP-related knowledge for healthcare providers, communication strategies and psychosocial support were only taught in two programs, and FP-related ethical and legal issues were only mentioned in one program.…”
Section: Discussionmentioning
confidence: 94%
“…According to another series of studies by our research team, as can be seen from a survey of 332 cancer patients, [15] 77.8% of patients realized that tumors and their treatment would damage fertility, 27.7% of patients worried that tumors would affect the DNA of offspring, but 71.1% of patients still do not know the existence of sperm banks. Additionally, the knowledge of FP by medical staff was also limited.…”
Section: Resultsmentioning
confidence: 99%
“…[ 6 ] However, one study in China showed that most of oncologists never informed their patients about FP and only a few know correct methods and institutions for FP. [ 7 8 ] In Indonesia, FP options have been recently considered by reproductive HCPs; however, there have been no surveys addressing specialists' awareness and attitudes toward FP for cancer patients. This research is the first study in Indonesia that reports the findings of a nationwide survey of Indonesian specialists and other HCPs regarding their awareness and attitudes toward FP in cancer patients.…”
Section: Discussionmentioning
confidence: 99%